Student satisfaction survey: A key for quality improvement in the higher education institution - Anita Kanwar; Meghana Sanjeeva (Journal of Innovation and Entrepreneurship, 2022)
India has witnessed a rapid expansion in the higher education institutions and with this fast pace of growth day by day, competition has set in among the institutes. Before taking admission in an institution student assess the facilities and standard of the institution by referring to the website, other admission portals and by taking peer opinion and public perception. Educational institutions around the world are now requesting students' feedback on all elements of academic life in the form of a satisfaction feedback questionnaire. The goal of this research is to describe the development and implementation of a survey to assess undergraduate and postgraduate student satisfaction. The Student Satisfaction Survey is a useful and effective instrument that tries to focus resources on areas, where there is low satisfaction but high importance. This paper gives detailed information about the methodology, calculation and outcome of the exercise utilizing Likert scale analysis. With the recent emerging trends, this innovative method offers flexibility to integrate more parameters, group certain parameters to get feedback on a particular issue and transmute the type of questions with changing environment and structure. The analysis is done using a statistical method. The survey result directly highlights the importance and flexibility of method to evaluate overall satisfaction, satisfaction cognate to a single parameter and satisfaction for questions grouped together underlining some paramount aspects of higher education.
Keywords: 650; Feedback; Higher education institution; Postgraduate; Student satisfaction; Undergraduate